Kajian Pertumbuhan Diameter dan Tinggi Pohon Jelutung (Dyera polyphylla (Miq.) di Kota Palangka Raya: Study on Diameter and Height Growth of Jelutung in Palangkaraya Central Kalimantan - Gaman, Sampang; Sukarna, Raden Mas; Rotinsulu, Johanna Maria; Penyang, Penyang; Nuwa, Nuwa (HUTAN TROPIKA, 2025)
Peat swamp forests are dominated by local tree types that have economic value, such as ramin, merani, nyatoh and jelutung. Jelutung trees provide benefits in the form of wood and sap, in addition, swamp jelutung is an ideal type for the rehabilitation of peat swamp forests that are resistant to flooded peatlands. Based on the above problems, it is necessary to conduct a study to analyze the relationship between the growth of the diameter and height of the jelutung plant. This research was carried out in 2023 in community jelutung gardens in Palangka Raya City. The method used to study the growth dynamics of jelutung trees is carried out by purposive sampling, namely by selecting and determining jelutung trees based on the age class of jelutung trees with a sampling intensity of ±5% of the area or number of trees. The results of measuring the diameter and height of the tree were analyzed through a correlation regression test displayed in the form of tables and graphs. The results of the study at the location of the jelutung plantation in Bukit Tunggal Village showed that the relationship between the diameter and height of the tree in the farmer's garden 1 had a coefficient interval value of 0.9476 and the relationship between the diameter and height of the tree in the farmer's garden 2 showed a coefficient interval value of 0.9563. while the location of the jelutung plantation in Kalampangan Village showed the relationship between the diameter and height of the jelutung tree in the farmer's garden 1 with a coefficient interval value of 0, 9151, the relationship between the diameter and height of the tree in the farmer's garden 2 was 0.8277 and the relationship between the diameter and height of the tree in the farmer's garden 3, farmer 4 and farmer 5 was 0.79551. This value shows that there is a very strong and positive relationship between the two variables.